A simple architecture for high performance class-D audio amplifier with novel RC network as negative feedback loop - Nour El Imane Bellili; Khaled Bekhouche (Institute of Advanced Engineering and Science, 2022)
In this work, we have designed and simulated a proposed architecture and good performances single-ended class-D audio amplifier (CDA). The proposed circuit is build using pulse-width modulation (PWM). We have proposed a novel RC network as negative feedback loop attached to a second-order integrator to get free of high-frequency carrier ripples and to reach improved output accuracy, thus improved performance and efficiency. This proposed negative feedback loop extremely reduces total harmonic distortion plus noise (THD+N). We have used a passive second-order butterworth output filter. This circuit fulfills a power supply rejection ratio (PSRR) of 75 dB, a THD+N of 0.004%, 3 times less than attained by usual feedback loop. The proposed circuit with quiescent current of 0.02 mA, signal to noise ratio (SNR) of 89 dB, and peak efficiency of 90% is running at 400 kHz switching frequency. The results of simulation demonstrate that this circuit significantly keeps up with the performance of other circuits but taking advantage of its simple architecture.